Agriculture–nutrition linkages with heterogeneous, unobserved returns and costs: Insights from Tajikistan - Takeshima, Hiroyuki; Akramov, Kamiljon T.; Park, Allen; Ilyasov, Jarilkasin; Liu, Yanyan; Ergasheva, Tanzila (International Association of Agricultural Economists, 2020)
Agriculture‐nutrition linkages (ANLs) have been increasingly investigated in the literature. However, nutritional returns and costs of household agricultural production practices (APPs) in semi‐subsistence settings are poorly understood. We fill these knowledge gaps using pooled cross‐section datasets in Tajikistan, where semi‐subsistence farming and undernutrition coexist despite relatively good agricultural infrastructure and education systems. Agricultural diversification, yield enhancement, production expansion are positively associated with various nutritional outcomes, particularly in areas with poor food market access. Decomposition exercises suggest that nutritional returns and costs of these APPs vary across households, and the adoption of APPs is driven by the expected nutritional returns. In Tajikistan, improving nutrition through household ANLs requires growing the smallholder agricultural sector in multiple dimensions, including diversification, intensification, and expansion, while also understanding better the pathways of ANLs and addressing bottlenecks at appropriate stages of such pathways.